Leveraging public data: Changes in local economic distress and drug overdose deaths at the county level, 2000 - 2019 - Saba, Shaddy K.; Lavista Ferres, Juan M.; Weeks, Bill (International Journal of Public Health, 2025)
Indices of local economic distress, including local-area unemployment, poverty, low income, and low education, have been linked with lower healthcare quality, higher care costs, and poorer health [1]. There exist vast county-level disparities in economic conditions across the U.S., and counties with greater economic distress demonstrate inequities in health and social determinants of health [2]. Improvements in local economic conditions predict better health including reduced mortality [3] and improved cardiovascular outcomes [4]. The early 2000s saw a reduction in life expectancy, driven by an increase in deaths by drug overdose, suicide, and chronic liver disease [5]. These have been termed “deaths of despair;” while overdose deaths during the early 2000s’ opioid epidemic are attributed to complex factors including overprescribing, there are also likely socioeconomic determinants including distressed local economic conditions [5]. We leveraged two public data sources [the Centers for Disease Control and Prevention’s Wide-ranging Online Data for Epidemiologic Research (CDC WONDER; wonder.cdc.gov) database and the Economic Innovation Group’s Distressed Communities Index (DCI; eig.org/dci-fact-sheet)] to examine whether local economic distress and changes in distress were associated local drug overdose. This approach highlights how public data can be used to explore critical public health questions.